Evaluation of Caesarean Section Rates Utilising Robson’s Classification System: A Retrospective Observational Study from Eastern India - Vaibhav Shivaji Patil; Sohini Bhattacharya; Selim Akhtar (Indian Journal of Neonatal Medicine and Research)
Introduction: The increasing trends in Caesarean Section (CS) globally are undoubtedly alarming. Although the World Health Organisation (WHO) did not specify an ‘optimal’ rate in 2015, it is essential to study caesarean deliveries to understand the causes of the rising rates and prevent unnecessary CS. Robson’s classification system, recommended by the WHO, is the most appropriate tool for this purpose. Aim: To identify groups of women according to Robson’s Ten-group Classification System (TGCS) assess the complications and morbidities of both mothers and neonates, and analyse the indications for caesarean delivery. Materials and Methods: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology at Jalpaiguri District Hospital, Jalpaiguri, West Bengal, India, from April 2021 to March 2022. A total of 350 women who underwent CS were included in the study, The study population was divided into ten groups (1-10) according to Robson’s TGCS. The variables assessed included the age group and gravidity status of the mothers, indications for CS, and maternal and neonatal mortality and morbidity. Data were collected from the operating theatre register, mother and baby bed head tickets, sick neonatal care unit admission registers, and Critical Care Unit (CCU)/High Dependency Unit (HDU) admission registers at one-month intervals. Frequencies and percentages were calculated. Results: Most of the women (120 mothers) belonged to the age group of 20-24 years. Out of the total, 206 mothers (59%) were primigravida, while 144 (41%) were multigravida. A total of 73 mothers (20.9%) fell under Group 2 of Robson’s classification system, followed by Group 1 50 (14,3%) and Group 4 49 (14%). The least number of women were in Group 7 11 (3.1%). Oligohydramnios was the indication for 45 mothers (12.8%). Total 10 mothers required HDU admission, and two required CCU admission postoperatively. There were no maternal deaths and no cases of peripartum hysterectomy. One birth was stillborn, and there were 13 neonatal deaths among 349 live neonates. Conclusion: In present study, authors found that most of the mothers were primigravida and fell under Group 2 of Robson’s classification system. The most common indication for CS was foetal distress, followed by a history of previous CS.